Мультифрактальний аналiз вiдбиткiв крапель розпиленого дизельного палива рiзного хiмiчного складу - Kolodnytska, R. V.; Kryzhanivskyy, V. B.; Moskvin, P. P. (Publishing house "Academperiodika", 2019)
The multifractal analysis of the photos of droplet marks left by droplets of dispersed diesel fuels on the surface of a glass plate covered with a soot layer is performed. The dependences of the parameters for the multifractal spectra of mark areas on the component ratio in a mixture of diesel fuel and biofuels are found. The correspondence of the multifractal characteristics to their canonical forms is demonstrated. The developed numerical method can be used for the quantitative evaluation and analysis of the parameters characterizing the spatial fractal forms generated in air-fuel aerosols. Quantitative relationships between the parameters of multifractal spectra and the chemical composition of dispersed fuels are revealed.